A VALIDATED STABILITY INDICATING HIGH PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR SIMULTANEOUS DETERMINATION OF METFORMIN HCL AND DAPAGLIFLOZIN IN BULK DRUG AND TABLET DOSAGE FORM - Mohammad Yunoos; GOWRI SANKAR D (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: A simple and precise stability indicating reversed-phase high-performance liquid chromatography method was developed and validated for the simultaneous determination of metformin (MET) hydrochloride and dapagliflozin (DAP) in bulk and pharmaceutical dosage form. Methods: Chromatography was carried out on hypersil BDS C18 (250 mm Ã— 4.6 mm, 5 Î¼ particle size) column containing mobile phase of buffer (0.1% orthophosphoric acid) adjusted to pH 6.8 with triethylamine:acetonitrile in the ratio of 50:50%/v/v at a flow rate of 1 ml/minutes. The analyte was monitored using photodiode array detector at 240 nm. Results: The retention time was found to be 2.791 minutes and 3.789 minutes for MET hydrochloride and DAP respectively. The proposed method was found to be having linearity in the concentration range of 85-510 Î¼g/ml for MET (r2=0.99995) and 0.5-3.0 Î¼g/ml for DAP (r2=0.99978), respectively. The mean % recoveries obtained were found to be 99.66-100.23% for MET and 99.61-100.38% for DAP respectively. Stress testing which covered acid, base, peroxide, photolytic and thermal degradation was performed on under test to prove the specificity of the method and the degradation was achieved. The developed method has been statistically validated according to ICH guidelines. Conclusion: Thus, the proposed method can be successfully applied for the stability indicating the simultaneous determination of MET hydrochlorideand DAP in bulk and combined tablet dosage form and in the routine quality control analysis. Keywords: Dapagliflozin, Metformin hydrochloride, Reversed-phase high-performance liquid chromatography, Forced degradation, Method validation.